Living Qur’an: Pembacaan Surat Al-Waqi’ah dan Al-Mulk - Suci Rahmadhani Siregar; Hasiah Hasiah; Desri Ari Enghariano (IAIN Padangsidimpuan, 2021)
The application of reading the letters of al-Waqi'ah and al-Mulk at the Al Ansor Manunggang Julu Islamic Boarding School, Southeast Padangsidimpuan District, Padangsidimpuan City. The practice of applying Sutar recitation is one of the social responses of a particular community or group of people in perceiving the presence of the Qur'an. This study discusses the practice and meaning of the application of reading al-Waqi'ah and al-Mulk letters at the al-Ansor Manunggang Julu Islamic Boarding School, Kec. Padangsidimpuan Southeast Padangsidimpuan City. The aim is to find out the practice and meaning of the application of reading al-Waqi'ah and al-Mulk letters at the al-Ansor Manunggang Julu Islamic Boarding School, Kec. Padangsidimpuan Southeast Padangsidimpuan City. In this paper, the writer uses a qualitative descriptive method with data collection techniques that the author does, namely observation, interviews and documentation. Then take books related to this research, such as the book of theresearch methodology Living Qur'an and Hadithby Sahiron Syamsudin. The results of the study, it can be seen that the application of reading letters al Waqi'ah and al-Mulk is the idea of the female student organization management that has lasted for 7 years and it is required for all female students to take part in the reading of Surat al-Waqi'ah which is carried out after the Fajr prayer and Surah al-Mulk is carried out after the Isha prayer. Initially the students felt compelled to do it, as time went on there were certain benefits that were obtained such as peace of mind, comfort, ease in dealing with problems that came, increasing parental submissions, not feeling deprived, and being able to control emotions.